Defesas contra herbivoria e descritores da vegetação: relações com variáveis edáficas em uma área de cerrado - Dantas, Vinícius de Lima (Universidade Federal de São Carlos, 2010)
Together with fire and climate changes, soil is considered a major determinant in the Braziliancerrado, the richest savanna in the world. Soil can influence plants by filtering species capableof acquiring resources and compete for them, but can also influence plant patterns ofallocation in defense against herbivory. Although many studies focused on plant soilrelationship in cerrado, few focused on the influence of soil at fine scale. We expectedcommunity descriptors, such as floristic composition, richness, evenness, diversity, and totalabundance to be related to soil features at fine scale within a physiognomy. We also expectedplants on nutrient-poor soils to present higher anti-herbivory defenses. In a cerrado site, weplaced 100 contiguous 25 m2 plots, in which we identified all woody individuals, measuredsoil variables and the following leaf traits: specific leaf area, C:N ratio, water content,toughness, trichomes, latex, and presence of tannins, alkaloids, and terpenoids. We did apartial redundancy analysis to test for relationship between soil features and floristiccomposition, controlled for spatial dependence. We also did multiple regression or spatialautoregressive models to test for relationships between soil features and: (1) the abundance ofthe five commonest species, (2) total abundance, (3) richness, (4) evenness, and (5) diversityand to predict defense traits based on soil features. We found no relationship between soil andfloristic composition, probably due to functional redundancy or limited dispersal. Organicmatter was positively related to Myrsine umbellata, the most abundant species, and totalabundance, and negatively related to evenness, what suggests positive feedbacks to cause thedominance by Myrsine umbellata. We also found a positive relationship between sum of basisand species richness, probably reflecting a fertility gradient. Contrary to our expectations, wefound no relationship between total defenses and total soil fertility or soil variables, whatcould result from low variability in soil fertility at fine scale or of high phenotypic variability.Presence of tannins was positively related to organic matter, possibly reflecting a strategytowards lower tolerance due to low reserve allocation or interactions with other resources.However, since tannins decrease leaf decomposition rates, organic matter could beaccumulating in soil. Overall, we suggest that soil is an important factor structuring cerradocommunity even at fine scales and that the dominance of cerrado species could be related topositive plant-soil feedbacks.
Keywords: Ecologia de comunidades; Herbivoria; Autocorrelação espacial; Solos; Matéria orgânica; Modelos autorregressivos; Myrsine umbellata; Riqueza; Soma de bases; Resistência contra herbivoria; Autoregressive models; Anti-herbivory resistance; Myrsine umbellata; Organic matter; Spatial autocorrelation; Species richness; Sum of basis; CIENCIAS BIOLOGICAS::ECOLOGIA